Relationships Between Task Constraints, Visual Constraints, Joint Coordination and Football-Specific Performance in Talented Youth Athletes: An Ecological Dynamics Approach - Heuvelmans, Pieter; Di Paolo, Stefano; Benjaminse, Anne; Bragonzoni, Laura; Gokeler, Alli (Perceptual and Motor Skills)
Individual performance in team sports is a multifactorial reflection of how well a player can cope and accomplish tasks in varied playing situations. Thus, performance analysis should not only focus on outcomes, but also on underlying mechanisms of those outcomes. We adopted principles of the ecological dynamics approach (EDA) to investigate the effect of introducing constraints on players’ joint coordination responses for a football-specific performance drill outcome. Seventeen talented youth football (soccer) players performed a football-specific drill under different conditions: basic constraints, additional defender dummies, stroboscopic glasses, and a combination of the latter two constraints. We recorded these players’ execution time, passing accuracy, and lower extremity joint kinematics. We calculated joint coordination for hip-knee, knee-ankle, and trunk-hip couplings. The added constraints negatively affected execution time and passing accuracy, and caused changes in joint coordination. Furthermore, we identified a relationship between execution time and joint coordination. This study serves as an example how the EDA can be adopted to investigate mechanisms that underlie individual performance in team sports.

Comparing the Effects of Differential and Visuo-Motor Training on Functional Performance, Biomechanical, and Psychological Factors in Athletes after ACL Reconstruction: A Randomized Controlled Trial - Gholami, Fatemeh; Letafatkar, Amir; Moghadas Tabrizi, Yousef; Gokeler, Alli; Rossettini, Giacomo; Ghanati, Hadi Abbaszadeh; Schöllhorn, Wolfgang Immanuel (Journal of Clinical Medicine)
Variation during practice is widely accepted to be advantageous for motor learning and is, therefore, a valuable strategy to effectively reduce high-risk landing mechanics and prevent primary anterior cruciate ligament (ACL) injury. Few attempts have examined the specific effects of variable training in athletes who have undergone ACL reconstruction. Thereby, it is still unclear to what extent the variations in different sensor areas lead to different effects. Accordingly, we compared the effects of versatile movement variations (DL) with variations of movements with emphasis on disrupting visual information (VMT) in athletes who had undergone ACL reconstruction. Forty-five interceptive sports athletes after ACL reconstruction were randomly allocated to a DL group (n = 15), VT group (n = 15), or control group (n = 15). The primary outcome was functional performance (Triple Hop Test). The secondary outcomes included dynamic balance (Star Excursion Balance Test (SEBT)), biomechanics during single-leg drop-landing task hip flexion (HF), knee flexion (KF), ankle dorsiflexion (AD), knee valgus (KV), and vertical ground reaction force (VGRF), and kinesiophobia (Tampa Scale of Kinesiophobia (TSK)) assessed before and after the 8 weeks of interventions. Data were analyzed by means of 3 × 2 repeated measures ANOVA followed by post hoc comparison (Bonferroni) at the significance level of p ≤ 0.05. Significant group × time interaction effects, main effect of time, and main effect of group were found for the triple hop test and all eight directions, SEBT, HF, KF, AD, KV, VGRF, and TSK. There was no significant main effect of group in the HF and triple hop test. Additionally, significant differences in the triple hop test and the seven directions of SEBT, HF, KF, KV, VGRF, and TSK were found between the control group and the DL and VMT groups. Between group differences in AD and the medial direction of SEBT were not significant. Additionally, there were no significant differences between VMT and the control group in the triple hop test and HF variables. Both motor learning (DL and VMT) programs improved outcomes in patients after ACL reconstruction. The findings suggest that DL and VMT training programs lead to comparable improvements in rehabilitation.

Conclusion-based Counter-Argument Generation - Alshomary, Milad; Wachsmuth, Henning (Proceedings of the 17th Conference of the European Chapter of the Association for Computational Linguistics)
In real-world debates, the most common way to counter an argument is to reason against its main point, that is, its conclusion. Existing work on the automatic generation of natural language counter-arguments does not address the relation to the conclusion, possibly because many arguments leave their conclusion implicit. In this paper, we hypothesize that the key to effective counter-argument generation is to explicitly model the argument‘s conclusion and to ensure that the stance of the generated counter is opposite to that conclusion. In particular, we propose a multitask approach that jointly learns to generate both the conclusion and the counter of an input argument. The approach employs a stance-based ranking component that selects the counter from a diverse set of generated candidates whose stance best opposes the generated conclusion. In both automatic and manual evaluation, we provide evidence that our approach generates more relevant and stance-adhering counters than strong baselines.

Concurrent validation of the Xsens IMU system of lower-body kinematics in jump-landing and change-of-direction tasks - Nijmeijer, Eline M.; Heuvelmans, Pieter; Bolt, Ruben; Gokeler, Alli; Otten, Egbert; Benjaminse, Anne (Journal of Biomechanics)

Hermann Lotze’s Influence on the Twentieth Century Philosophy - Milkov, Nikolay

Bertrand Russell’s Philosophical Logic and its Logical Forms - Milkov, Nikolay (Athens Journal of Philosophy)
From 1901 to 1919, Russell persistently maintained that there were two kinds of logic and distinguished between one and the other as mathematical logic and philosophical logic. In this paper, we discuss the concept of philosophical logic, as used by Russell. This was only a tentative program that Russell did not clarify in detail; therefore, our task will be to make it explicit. We shall show that there are three (-and-a-half) kinds of Russellian philosophical logic: (i) “pure logic”; (ii) philosophical logic investigating the logical forms of propositions; (iii) philosophical logic exploring the logical forms of facts: in epistemology and in the external world. In particular, Russell’s program or philosophical logic of the facts of the external world remained less than sketchily outlined.
Keywords: Russell; mathematical logic; philosophical logic; Wittgenstein

Calibration of Large Coherent MIMO Radar Arrays: Channel Imbalances and 3D Antenna Positions - Greiff, Christian; Mateos-Núñez, David; Simoni, Renato; González-Huici, Maria; Kruse, Stephan; Scheytt, J. Christoph; Kolk, Karl; Höller, Christian; Kurz, Heiko Gustav; Meinecke, Marc-Michael; Gisder, Thomas (2023 24th International Radar Symposium (IRS))
One of the main challenges for next generation automotive radars is the improvement of angular resolution to a sub-degree level. In this context, wide aperture automotive radars of 1m length or more and resolution close to 0.1° in azimuth and 0.5° in elevation could be beneficial. To enable coherent processing of arrays with such large aperture, prior (i.e offline) and online calibration are necessary: channel imbalances (gains and phases) and three dimensional coordinates of transmit and receive elements need to be determined. We propose a calibration strategy based on alternating steps between the two subtasks of i) channel imbalance estimation with ‘known’ array positions, by applying a singular value decomposition to the resulting tensor calculus problem; and ii) antenna position estimation with ’known’ channel imbalances, by numerically maximizing the Bayesian posterior probability; in both cases operating on range/Doppler snapshots of disjoint targets (with potentially unknown locations). Simulation studies based on the parameters of a MIMO 8x6 linear sparse array show promising results as long as the initial position errors do not exceed half a wavelength (2mm), beyond which we observe strong effects of ambiguity. Experimental results with real measurements show that after calibration in laboratory conditions, our MIMO 8x6 demonstrator with 50cm aperture is able to resolve two targets at the same range with angular separation at least as close as 0.4°.

Distributed System Architecture for Software-Defined Radio / Radar with Optical Signal Distribution - Kruse, Stephan; Kneuper, Pascal; Schwabe, Tobias; Meinecke, Marc-Michael; Kurz, Heiko G.; Scheytt, J. Christoph
In this paper we present a new system architecture for software-defined radio / radar with optical signal distribution. The proposed architecture allows to transmit the optical carrier and an arbitrary IQ signal on the same fiber from a base station to wireless transmitters using a single laser. Furthermore, we can reuse parts, and under special conditions, also the complete optical output of the base station for the IQ return path from the wireless receiver frontends to the base station. Avoiding multiple lasers and fibers for the distribution of the carrier and arbitrary signal from the base station to the frontend, and avoiding the laser diode for the IQ return path from receiver frontends to the base station reduces the hardware effort significantly. Finally, the system architecture allows to integrate all components of the optoelectronic wireless frontend in a single chip using silicon photonics technology.

Analysis and Simulation of a Coherent FMCW Lidar-Photonic Radar Combined Sensor System for Large Aperture Phased Array MIMO - Kruse, Stephan; Meinecke, Marc-Michael; Kneuper, Pascal; Schwabe, Tobias; Kurz, Heiko G.; Scheytt, J. Christoph (2023 20th European Radar Conference (EuRAD))

A Narrowband Four-Quadrant Electro-Optical Mixer for Microwave Photonics - Kruse, Stephan; Greitens, Jan C.; Schwabe, Tobias; Kneuper, Pascal; Kurz, Heiko G.; Scheytt, J. Christoph (IEEE Microwave and Wireless Technology Letters)

Nonlinear S-Parameter Behavioral Model of a Photonic Radar Transceiver Chipset for Automotive Applications - Kruse, Stephan; Schwabe, Tobias; Kneuper, Pascal; Meinecke, Marc-Michael; Kurz, Heiko G.; Scheytt, J. Christoph
This paper presents a method to model monolithically integrated photonic radar transceiver (TRX) with optical local oscillator (LO) distribution in silicon germanium (SiGe) electronic photonic integrated circuits (EPICs). The model proposed approximates the behavior of the nonlinear scattering (S)-parameters and noise figure of each building block of the TRX chipset by Laplace polynomials and hyperbolic tangent functions. The modular approach of the model allows to optimize hardware components with respect to the entire TRX system, and fault identification with reduced computational effort. The proposed method is validated using the first monolithically integrated photonic radar transceiver chipset and shows excellent agreement with the post layout simulation results and, including the photodiode (PD) bandwidth (BW) degradation, also with the measurements.

A 28-Gb/s 27.2 mW NRZ Full-Rate Bang-Bang Clock and Data Recovery in 22 nm FD-SOI CMOS Technology - Iftekhar, Mohammed; Nagaraju, Harshan; Kneuper, Pascal; Sadiye, Babak; Müller, Wolfgang; Scheytt, J. Christoph (BCICTS 2023 IEEE BiCMOS and Compound Semiconductor Integrated Circuits and Technology Symposium)

Alterations of postural control across the menstrual cycle – A systematic review - Pohle, Carina; Paschen, Linda; Baumeister, Jochen (Gait & Posture)

Alterations of postural control across the menstrual cycle – A systematic review - Pohle, Carina; Paschen, Linda; Baumeister, Jochen (Gait & Posture)
Keywords: Rehabilitation; Orthopedics and Sports Medicine; Biophysics

AnnoPy – Ein digitales Tool zur Förderung von Textkompetenzen. - Rezat, Sara; Scholle, Oliver (Medien im Deutschunterricht)

Mit digitalen Tools Peer-Feedback zu Texten geben. - Rezat, Sara (Deutsch 5-10)

Frömmigkeit als Antwort auf Krisen und Katastrophen? Die Erweckungsbewegung im 19. Jahrhundert in Lippe und der Lippische Gemeinschaftsbund - Pinsch, Jan Christian (Katastrophen. Religiöse Bildung angesichts von Kriegs- und Krisenerfahrungen im 19. und 20. Jahrhundert)

Die schriftbildliche Gestaltung von lexikalisch übernommenen Markennamen. Ein explorativer Wahrnehmungstest zum graduellen Entrenchment von Markennamen als multimodale Konstruktionen - Dübbert, Alexander (Beiträge zur Namenforschung)
Dieser Beitrag untersucht, inwiefern sich die kognitive Verankerung von der schriftbildlichen Gestaltung lexikalisch übernommener Markennamen nachweisen lässt. Dazu werden die Ergebnisse eines tachistoskopischen Wahrnehmungstests ausgewertet, bei dem einer Testgruppe die Schriftbilder (Logos) der Markennamen 'FÜR', 'Landliebe', 'MONSTER', 'GUT & GÜNSTIG', 'kinder' und 'ja!' mehrmals für Sekundenbruchteile (0,01s, 0,02s, 0,1s und 1,0s) und teils mit substituiertem Schriftzug präsentiert wurden. Insgesamt deutet die explorative Untersuchung – mit graduellen Abweichungen – in die Richtung, dass die Wahrnehmung des Schriftbilds zum Erkennen des dazugehörigen Markennamens führt. Dies ermöglicht die Schlussfolgerung, dass sich die getesteten Markennamen als multimodale Konstruktionen mit konstitutiver Schriftbildlichkeit qualifizieren.

Cognitive Training Improves Joint Stiffness Regulation and Function in ACLR Patients Compared to Healthy Controls - An, Yong Woo; Kim, Kyung-Min; DiTrani Lobacz, Andrea; Baumeister, Jochen; Higginson, Jill S.; Rosen, Jeffrey; Swanik, Charles Buz (Healthcare)
As cognitive function is critical for muscle coordination, cognitive training may also improve neuromuscular control strategy and knee function following an anterior cruciate ligament reconstruction (ACLR). The purpose of this case-control study was to examine the effects of cognitive training on joint stiffness regulation in response to negative visual stimuli and knee function following ACLR. A total of 20 ACLR patients and 20 healthy controls received four weeks of online cognitive training. Executive function, joint stiffness in response to emotionally evocative visual stimuli (neutral, fearful, knee injury related), and knee function outcomes before and after the intervention were compared. Both groups improved executive function following the intervention (p = 0.005). The ACLR group had greater mid-range stiffness in response to fearful (p = 0.024) and injury-related pictures (p = 0.017) than neutral contents before the intervention, while no post-intervention stiffness differences were observed among picture types. The ACLR group showed better single-legged hop for distance after cognitive training (p = 0.047), while the healthy group demonstrated no improvement. Cognitive training enhanced executive function, which may reduce joint stiffness dysregulation in response to emotionally arousing images and improve knee function in ACLR patients, presumably by facilitating neural processing necessary for neuromuscular control.
Keywords: Health Information Management; Health Informatics; Health Policy; Leadership and Management

Christliche Ethik: Der Klimawandel. Interpretationen - Unterrichtsmodell - Garske, Volker; Bürger, Markus; Hellgermann, Andreas; Jendt, Sebastian